Firstly we learn the standard quadratic equation,
ax²+bx+c=0
where a,b,c are real numbers.
Now solve the quadratic equation using the Complete the square method.
Rewriting part of the equation as a perfect square trinomial. If you complete the square on the generic equation ax² + bx + c = 0 and then solve for x,
ax²+bx=-c
x² +
=-c
add both the side
![((b)/(2a) )^(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/3v1wvgdku4t47u3q954is5pe85lc4c1i3f.png)
x² +
+
![((b)/(2a))^(2) = -(c)/(a) + ((b)/(2a))^(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/eu74x6qr4y2xdcsucjhgdxd5h2rsbaufsd.png)
`
take square root both the side
![x = \frac{-b+\sqrt{b^(2)-4ac}}{2a}](https://img.qammunity.org/2019/formulas/mathematics/middle-school/nuieixm9s6oruuk3akw43n77htucoqtx2e.png)
![x= \frac{-b-\sqrt{b^(2)-4ac}}{2a}](https://img.qammunity.org/2019/formulas/mathematics/middle-school/id7a86xl94eguzhn9p9lucmcti54gatsas.png)